Онейропоэтика сборника рассказов Николая Байтова „Зверь дышит” - Raspapou, Aliaksandr (Studia Rossica Posnaniensia, 2019)
The article attempts to trace the process in which the selected narratives, based on the poetics of dreams, are constructed. This analysis focuses on the stories The Beast and Don Delta from Nikolai Baitov’s latest collection of stories The Beast Breathes, published in 2014. In the stories which were chosen as the examples, the presence of oneiric forms is both the primary compositional principle and the element determining the story’s genre affiliation. It is shown that the basic principle for organizing the literary dream in the story The Beast is the use of the poetic trope of metabole. Experiment with form underlies Don Delta, the story that follows. This leads the author to create a new genre form – the rough draft of a dream. Through his specific means of organising the dream form, Baitov reveals new possibilities for language in constructing a literary dream, while at the same time illustrating a paradoxical interaction between “signifier” and “signified” as well as their potential for creating literary reality.